Determinan Nilai Perusahaan Sektor Energi Dengan Board Gender Diversity dan Leverage Sebagai Variabel Moderasi - Rama, Pandri Hanandya; Siswanti, Indra (Universitas Mercu Buana, 2025)
The study aims to determine how Environmental, Social and Governance (ESG), Intellectual Capital, and Financial Performance variables can affect Firm Value, by adding Board Gender Diversity and Leverage variables as moderating variables that are estimated to strengthen or weaken the impact of these factors. This study uses Agency Theory, Signaling Theory, and Legitimacy Theory to explain the mechanisms behind the influence of these variables. The study uses a panel data model with a sample of 10 companies in the energy sector that meet the criteria for obtaining an ESG score from Bloomberg for the period 2016-2023. The results of the study indicate that ESG have a significant negative effect on Company Value, Intellectual Capital has a significant positive effect on Company Value, and Financial Performance has no effect on Company Value. ESG have a significant positive effect when moderated by Leverage, but conversely, Intellectual Capital becomes a significant negative effect when moderated by Leverage. Financial Performance has a positive effect on Company Value, and this effect is significantly strengthened by Leverage, indicating that high profitability under high Leverage conditions is a strong signal for investors. Board Gender Diversity does not provide a significant moderating role in the relationship between Environmental, Social and Governance, Intellectual Capital, and Financial Performance on Company Value